OZONE BLEACHING AT NEUTRAL PH – A NEW CONCEPT - Carvalho, Fernando de (2006)
The effect of medium consistency ozone stage pH was evaluated for brown and oxygen delignified eucalyptus kraft pulp samples obtained from VCP - Luiz Antônio pulp mill. These samples were used as such or previously treated with the hot acid stage (A). The main objective of this study was to determine the viability of increasing the ozone stage pH aiming at decreasing bleaching variable costs. The ozone stage was studied in the pH range of 2.5-9.0, taking into account some important variables which affect ozone bleaching: (1) pulp kappa number entering the ozone stage, (2) reactivity of ozone towards lignin versus hexenuronic acids (HexA´s), (3) pulp treatments prior to ozone stage (acid hydrolysis), and (4) pulp treatments after the ozone stage (extraction or a chlorine dioxide stage).  Therefore, the impact of ozone stage pH was investigated in bleaching process such as Z/DEop vs AZ/DEop, Z/DEopD vs AZ/DEopD, Z/E vs AZ/E. The results were interpreted based on ozone stage efficiency and selectivity, and overall bleaching performance measured by the total bleaching chemical consumption required to achieve full brightness, pulp quality and environmental impact. It was concluded that the increase of ozone stage pH from 2.5 to 7.0 has a slightly negative impact on the efficiency and selectivity, measured after Z/DEop sequence, but this effect is not expressive in the end of Z/DEopD bleaching sequence. The increase of ozone stage pH from 2.5 to 7.0 in the sequence Z/DEopD is cost-effective at industrial level because it represents expressive reduction of sulphuric acid and caustic soda demand for pH control in the bleaching plant. These gain areas achieved without any significant changes in pulp quality and effluent load discharge. Nevertheless, the increase of ozone stage pH from 2.5 to 7.0 has a very high negative impact on the efficiency and selectivity for the Z/E and AZ/E processes and it is not recommended in such cases.